Chemical characterisation of palm kernel (Elaeis guineensis Jacq.), shea butter (Vitellaria paradoxa C.F. Gaertn.) and sesame (Sesamum indicum L.) seed oils as ingredients in breeding broiler diets - Adeyemi, A. A.; Ogunwole, O. A; Oladimeji, S. O. (Nigerian Journal of Animal Science, 2023)
Lipids are important to both humans and livestock where they play important role as an excellent source of energy and enhances the absorption of fat-soluble vitamins. However, oils are used in formulation without any considerations given to the peculiarities of their innate constituents particularly, vitamin, fatty acids and phytochemicals. Thus, the basis of these determinations. Three lipids: palm kernel oil (PKO), shea butter (SB) and sesame seed oil (SSO), were analyzed chemically in triplicate using standard methods. Results showed that SB had the highest (p<0.05) peroxide value (meq/kg) of 7.4 while PKO (0.7) and SSO (0.3) were similar (p>0.05). The iodine values (g/100g) of the lipids were not significantly different (p>0.05). The saponification value (mgKOH) of PKO (249.9) was significantly higher than SBO (190.9) and SSO (15.8) while the acid value (mgKOH/g) of SBO (10.6) was significantly lower (p<0.05). The αtocopherol of SBO was 119.2 µg/mL which was significantly higher (p<0.05) than 69.6 µg/mL in SSO and 24.4µg/mL in PKO while there were significant variations (p<0.05) in the fatty acid composition of the oils. Analyses revealed the oils possessed variable chemical characteristics; while PKO would be most appropriate for soap production, SBO and SSO would be more susceptible to rancidity.